Ferroelectric properties of Pb(Zr0.52Ti0.48)O 3-Bi3.25La0.75Ti3O12 ceramics - Thongmee N. (2014)
The ceramic samples of compound (1 - x)Pb(Zr0.52Ti 0.48)O3-xBi3.25La0.75Ti 3O12 (when x = 0, 0.03, 0.05, 0.07, 0.10, 0.15 and 0.20) were prepared by a solid-state mixed oxide method. X-ray diffraction analysis showed that complete solid solutions occurred for all compositions. Perovskite phase with tetragonal crystal structure and corresponding lattice distortion was observed. Scanning electron micrographs of sample surfaces showed equiaxed grains for all compositions. Ferroelectric measurements revealed that the addition of small amount of BLT (x = 0.03) showed high remanent polarization (∼33.5 μC cm-2) and low coercive field (∼2.74 kV mm -1). Further increasing BLT content could maintain ferroelectric properties of PZT-BLT ceramics. Based on this study, ferroelectric properties of this PZT-BLT ceramic system can be improved for being further used in ferroelectric memory applications. © 2011 Elsevier Ltd and Techna Group S.r.l.